Negotiating trade : developing countries in the WTO and NAFTA / edited by John S. Odell. - Odell, John S., 1945- (Cambridge University Press, 2006)
Negotiations between governments shape the world political economy and in turn the lives of people everywhere. Developing countries have become far more influential in talks in the World Trade Organization, including infamous stalemates in Seattle in 1999 and Cancún in 2003, as well as bilateral and regional talks like those that created NAFTA. Yet social science does not understand well enough the process of negotiation, and least of all the roles of developing countries, in these situations. This 2006 book sheds light on three aspects of this otherwise opaque process: the strategies developing countries use; coalition formation; and how they learn and influence other participants' beliefs. This book will be valuable for many readers interested in negotiation, international political economy, trade, development, global governance, or international law. Developing country negotiators and those who train them will find practical insights on how to avoid pitfalls and negotiate better.